2022
DOI: 10.1172/jci159179
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as therapeutic targets in cardiovascular disease

Abstract: The discovery of microRNAs and their role in diseases was a breakthrough that inspired research into microRNAs as drug targets. Cardiovascular diseases are an area in which limitations of conventional pharmacotherapy are highly apparent and where microRNA-based drugs have appreciably progressed into preclinical and clinical testing. In this Review, we summarize the current state of microRNAs as therapeutic targets in the cardiovascular system. We report recent advances in the identification and characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 206 publications
0
79
0
1
Order By: Relevance
“…Given miR-34 and other miRNAs are ubiquitously expressed, it will be important to target organs or cell types specifically, for example with antibody or vector-based approaches [12,73]. The application of LNA-based antimiR therapies in preclinical animal models has been established in multiple disease settings [74][75][76], and recently in a setting of diabetesinduced heart disease and cardiac dysfunction [77]. Several studies have demonstrated efficacy and safe use of LNA-based antimiR therapies in human clinical trials, including miravisen (targeting the liver expressed miR-122 for the treatment of hepatitis C [13]), In previous work from us and other investigators, it had been shown that inhibiting miR-34a provided cardiac protection in settings of moderate cardiac pathology including aging [23], a model of moderate pressure overload-induced hypertrophy [18], acute myocardial infarction [23], and dilated cardiomyopathy [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given miR-34 and other miRNAs are ubiquitously expressed, it will be important to target organs or cell types specifically, for example with antibody or vector-based approaches [12,73]. The application of LNA-based antimiR therapies in preclinical animal models has been established in multiple disease settings [74][75][76], and recently in a setting of diabetesinduced heart disease and cardiac dysfunction [77]. Several studies have demonstrated efficacy and safe use of LNA-based antimiR therapies in human clinical trials, including miravisen (targeting the liver expressed miR-122 for the treatment of hepatitis C [13]), In previous work from us and other investigators, it had been shown that inhibiting miR-34a provided cardiac protection in settings of moderate cardiac pathology including aging [23], a model of moderate pressure overload-induced hypertrophy [18], acute myocardial infarction [23], and dilated cardiomyopathy [21].…”
Section: Discussionmentioning
confidence: 99%
“…The application of LNA-based antimiR therapies in preclinical animal models has been established in multiple disease settings [74][75][76], and recently in a setting of diabetesinduced heart disease and cardiac dysfunction [77]. Several studies have demonstrated efficacy and safe use of LNA-based antimiR therapies in human clinical trials, including miravisen (targeting the liver expressed miR-122 for the treatment of hepatitis C [13]), cobomarsen (an inhibitor of miR-155 in patients with T-cell lymphoma [78]), and MRG-110 (an inhibitor of miR-92a-3p, which is known to have a role in cardiovascular disease and wound healing [79]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is plentiful evidence suggesting that miRNAs regulate cardiac homeostasis and thus may serve as a diagnostic tool and/or therapeutic target [ 21 ]. Several miRNAs targeting mRNA-encoding proteins involved in cardiac fibrosis are currently being assessed for their potential use as therapeutic targets, but these approaches are still at an early stage [ 22 ]. Therefore, more information is needed to decipher the complicated interactions between miRNAs and the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of miRNAs is based on the knowledge of specific miRNA families involved in several biological processes [10] that are dysregulated in different pathologies, such as cardiovascular diseases [11][12][13][14][15], viral infections [16,17], metabolic diseases [18], diabetes [19], stress-related diseases [20][21][22] and cancer [23]. For this reason, it is conceivable that a molecular therapy takes advantage of their use.…”
Section: Introductionmentioning
confidence: 99%